Investigation of Cnidium monnieri compounds as phosphodiesterase-5 antagonists in erectile dysfunction via molecular docking and dynamic simulation - Damilola Alex Omoboyowa (Informatics in Medicine Unlocked, 2024)
This study aimed at evaluating the inhibitory potential of bioactive compounds from C. monnieri and predicting lead compounds for achieving and maintaining penile erection through computational models. A total of 79 compounds were retrieved for the plant through public repositories, phosphodiesterase-5 (PDE-5) was retrieved from the data bank for proteins (PDB). The molecular docking, free binding energy calculation, pharmacophore modeling and molecular dynamic simulation were performed using Schrodinger suite (2017–1). The quantum chemical calculation was also carried out with Spartan 14 computational software. Among the 79 compounds virtually screened against Phosphodiesterase-5 (PDE-5), eight (8) bioactive compounds showed potent antagonist against PDE-5 with varying binding scores comparable to that of Sildenafil (co-crystalized ligand). Monnieriside (−10.625 kcal/mol), Diosmetin (−10.041 kcal/mol and Isogosferol (−10.038 kcal/mol) were observed to have the best docking score comparable with Sildenafil (−11.872 kcal/mol). The fitness score range of 0.982–1.941 confirmed the validation of the docking scores using e-pharmacophore hypothesis. The result of the MD simulation reveals better stability of hit compound-protein complex (Monnieriside A-PDE-5) compared with the Sildenafil-PDE-5 complex. None of the hit compounds violated more than one rule of five and within the reference range for pharmacokinetics parameters. The quantum mechanics estimation revealed the hit molecules possess proton accepting and donating potential therefore, possess antagonistic potential. Based on the results from this study, the three top binding compounds may be predicted as potent inhibitors of PDE-5 and could use as lead compound for discovery of potent drugs for erectile dysfunction.